2008
DOI: 10.1038/nature07527
|View full text |Cite
|
Sign up to set email alerts
|

The replisome uses mRNA as a primer after colliding with RNA polymerase

Abstract: Replication forks are impeded by DNA damage and protein-nucleic acid complexes such as transcribing RNA polymerase. For example, head-on collision of the replisome with RNA polymerase results in replication fork arrest. However, co-directional collision of the replisome with RNA polymerase has little or no effect on fork progression. The current study examines co-directional collisions between a replisome and RNA polymerase in vitro. Surprisingly, we find that the E. coli replisome utilizes the RNA transcript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
188
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(200 citation statements)
references
References 50 publications
10
188
2
Order By: Relevance
“…However, they can only rarely result in fork collapses, which are highly damaging to cells (3,(7)(8)(9)11). Our data suggest that Rho removes TEC ahead of replisomes, preventing collision, fork collapse, and DSB formation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, they can only rarely result in fork collapses, which are highly damaging to cells (3,(7)(8)(9)11). Our data suggest that Rho removes TEC ahead of replisomes, preventing collision, fork collapse, and DSB formation.…”
Section: Discussionmentioning
confidence: 86%
“…A recent report describes the role of transcription elongation factors DksA and GreA in preventing conflicts between replication and transcription (7,10). In vitro, replication forks that collapse after colliding with a codirectional TEC can restart, using an R-loop (RNA-DNA hybrid) from a transcription bubble as primer (11), although it is not known if this occurs in vivo.…”
mentioning
confidence: 99%
“…S2A). A truncated replication machinery potentially restarts replication from an R-loop, given that elegant in vitro experiments demonstrated that replication can restart from a purified E. coli replisome-RNAP complex, and that the replisome uses mRNA as a primer to reinitiate leading-strand synthesis after displacing a codirectional RNAP from DNA (56). One can speculate that RNAPI is no longer associated with the R-loop, a scenario that facilitates TIR without the need for factors that drive the displacement of RNAPs being head-on to a replisome (57).…”
Section: Which Factors and Mechanism Would Participate In Transcription-mentioning
confidence: 99%
“…If forks pause at such barriers and lose function, then replisome reloading, often via blocked fork processing by recombination enzymes, is required to resume genome duplication (4), an error-prone process associated with gross chromosomal rearrangements (5)(6)(7). However, pausing of replisomes does not necessarily lead to fork breakdown, because paused replisomes can continue duplication upon removal or bypass of the block (8)(9)(10)(11). The balance between resumption of replication versus breakdown of paused forks is therefore a critical factor in the maintenance of genome stability.…”
mentioning
confidence: 99%